Development Of A Learning Model Process Approach To Improve The Writing Skills Of Junior High School Students In Sundanese Language Subjects (Universitas Pamulang, 2025)
To produce interactive teaching materials that are fit for purpose, easy for students to learn and can be used for individual learning, to find out the effectiveness of similar teaching materials developed in English subjects. This type of research is a developmental research using the Borg & Gall model combined with the Dick & Carey model. The results of the development process show that expertise and testing carried out with expertise are excellent throughout the stages of product evaluation. The method used in this study is semi-empirical. The results of the hypothesis test showed that there was a significant difference between the learning outcomes of students taught with interactive learning media and without interactive media. This is shown by the results of data processing and the conclusion that the learning outcomes of the group of students taught with interactive learning media are higher than those learned without interactive learning media.